The Relationship Between Education and Economic Status in Social Stratification in Surabaya City - Dwina Rastri Juniar Krisanti (Multidisciplinary Journal of Social Sciences and Humanities, 2025)
This study aims to analyse and connect the role of education within social stratification and its structure, particularly focusing on the educational sector. Education is a fundamental necessity for the development of knowledge and preparation for the future. However, a significant issue arises among lower economic classes who struggle to afford education for their children due to financial constraints. In contrast, upper economic classes are more capable of enrolling their children in expensive or even international schools. This situation creates noticeable social disparities. Furthermore, in the job market, many companies tend to prioritize applicants with a university degree (S1) over those with only a high school diploma or less, such as elementary school graduates, who often find it difficult to secure employment. This inequality raises questions about whether educational attainment significantly influences one's future success. Does obtaining a higher degree guarantee a better quality of life compared to those who only complete junior or senior high school? The objective of this research is to analyze and link educational status with social stratification levels to determine whether expensive education guarantees a better future. This study uses a qualitative descriptive method, which emphasizes interpreting and understanding social phenomena in depth, supported by literature review. The analysis follows an inductive approach to uncover emerging patterns and themes. The research is grounded in Max Weber's theory of social status within socio-economic groups.